Some remarks on the extended Hartley-Hilbert and Fourier-Hilbert transforms of Boehmians - Al-Omari, Shrideh Khalaf Qasem; Kilicman, Adem (Hindawi Publishing Corporation, 2013)
We obtain generalizations of Hartley-Hilbert and Fourier-Hilbert transforms on classes of distributions having compact support. Furthermore, we also study extension to certain space of Lebesgue integrable Boehmians. New characterizing theorems are also established in an adequate performance.